Suitability of mangrove ecotourism in Payo Village, West Halmahera Regency: Kesesuaian Ekowisata Mangrove di Desa Payo, Kabupaten Halmahera Barat - Riyadi Subur; Abubakar, Salim; Susanto, Adi Norman (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
The uniqueness of the mangrove ecosystem is a potential that can be developed as an ecotourism destination. Ecotourism activities are one of the many alternatives to overcome environmental problems in the mangrove ecosystem. The research objective was to assess the suitability of mangroves as an ecosystem for the ecotourism area of ​​Payo Halmahera Barat Village. The research used a survey method, which is to directly measure the biophysical conditions of mangroves. The results showed that the suitability value of the mangrove ecosystem for ecotourism was 73.86%, with the "appropriate" or (S2) category.